Customer Perceptions of Bakery and Restaurant Brand Image - Sri Marini; Yayan Sugiarto; Nadilah Hanuun Iskandar (Gastronomy Tourism Journal, 2023)
The research objective of customer perception of brand image is to understand how brands are seen, perceived, and interpreted by consumers or target audiences. This research aims to explore the perceptions, associations, and images associated with the brand in the minds of consumers. Identifying brand image is very important because it can help companies or organizations. The problems faced by Resto are not as good as when it was originally launched. The number of business competitors in the same field can also be a problem. The method used is descriptive research using probability sampling and simple random sampling techniques. In this study the population was 5,489 people, with a significance of 10%, a sample of 100 respondents was obtained using slovin formula. The results showed that 16.4% of respondents had a positive view of the superiority of brand associations, while around 61.8% of respondents had a negative view, 22% of respondents were neutral. As for the strength of brand association, 13.7% of respondents have a positive view, 68.3% of respondents have a negative view, 14.7% of respondents have a positive view of the uniqueness of the Resto Bakery brand association, while around 68.6% of respondents have a negative view. Association Advantage is still lacking, Resto Bakery can consider strategies that focus on improving customer experience, clearer brand communication, and strengthening elements that generate positive associations with the brand. The strength of the Brand Association is not yet strong, Resto Bakery can consider strategies that focus more on strengthening brand elements, improving service or product quality, and conducting more effective brand communication to customers. Uniqueness of Brand Association is still lacking, can focus efforts on communicating and highlighting the elements that make their brand unique and different from competitors, and invite customers to experience that uniqueness firsthand.